THE EFFECT OF GOOD GOVERNANCE IMPLEMENTATION, FINANCIAL MANAGEMENT, QUALITY OF HUMAN RESOURCES, COMMUNITY PARTICIPATION AND SUPERVISION ON VILLAGE FINANCIAL ACCOUNTABILITY IN DELI SERDANG REGENCY - Agus Tan, Tengku Juhri (International Journal of Public Budgeting, Accounting and Finance, 2021)
This study aims to determine the effect of village financial accountability on the application of good governance, financial management, quality of human resources, community participation and supervision. This research is a quantitative study using primary data through questionnaires directly given to respondents, namely the village head, village secretary, village treasurer, village consultative body and village community, in villages located in Lubuk Pakam sub-district, Tanjung Morawa sub-district, Batang Kuis sub-district and Percut Sei Tuan sub-district, with a total of 35 villages, with a sampling technique that is purposive sampling. Test equipment used in this study is WarpPLs 3.0. The results showed that both partially and Goodness of Fit had a positive and significant effect on financial accountability with a significant value of less than 0.05.